PREVALENCE OF HARD TICKS Boophilas microplus . IN COWS IN SOME REGAONS OF AL-ANBAR GOVERNORATE - EZEDDIN A. ALBAYYAR; HUSSAM ALDIN A. MOHAMMED; SUAD SH. SHAHATHA (مجلة جامعة الانبار للعلوم الصرفة, 2014)
This study included survey for hard ticks Boophilas microplus . Infestations in cows at some areas in al-Anbar governorate by examining 2840 cows hide ,with different ages and from both sexes during the period December 2011 up to December 2012. Resalts revealed an optical in fastation 54.01% ,the in festation percent. In females was 62.54 % which was higher tham the in festation percent .In males which was 44.95 %. The rate of highest investation in age (month -<2) year was 71.59% and the lowest rate 21.68% was in cows at age of ( 8-<10) years with significant difference (p< 0.05) was conducted . The highest rate was 89,84.69% in May and June respectively and the lowest rate 16.66% in October with significant difference (p<0.05).